Efecto de cinco abonos orgánicos líquidos en el cultivo de pepino alaska Cucumis sativus L., en la parroquia Palma Roja, cantón Putumayo, provincia de Sucumbíos - Días Suin, Jesús Normandina (2015)
Red Palm in Putumayo Canton, province of Sucumbíos parish during the months of January to April 2015, the thesis project entitled "Effect five liquid organic fertilizers in the cultivation of cucumber Cucumis sativus L. variety Alaska, ran goals They were to evaluate the cucumber crop yield with application of five types of liquid organic fertilizers; determine the profitability of production of cucumber to the application of five types of liquid organic fertilizers; and share the results obtained from research to farmers in the sector. Treatments tested were: Biol (T1), manure tea (T2), wood vinegar (T3), fruit fertilizer (T4) and tea bocashi (T5), applied statistical design was randomized blocks with five treatments plus a control (T0) and three repetitions, giving a total of 18 experimental units. The variables evaluated were: percentage of germination, days to flowering, stem diameter at 20 days, number of fruits per plant, number of fruits per hectare, fruit length (cm), fruit diameter (cm), weight fruit per treatment (g), days to harvest and ultimately profitability. The results obtained were: in the germination percentage, values ranged from 76.07% (T0 and T2), to 90.63% (T3), for the variable plant height 20 days recorded data have a great variation between treatments, the greater height of the plant is recorded in treatments 5 and 4, with 67.07 cm and 66.90 cm, respectively, while the lowest height treatment 1 introduced with 8.88 cm; in stem diameter, it can be seen that the larger diameter presented as treatments 3, 4 and 5 (0.65 cm and following the first with 0.56 cm), and with smaller diameter with treatment 1 0.32 cm. Apparently, the effect of liquid manure treatments 4 and 5 are expressed both in height and stem diameter. The variable days to flowering that goes from 51 (T3) to 53 (T1) days. Regarding the number of fruits per plant and treatment stand treatments 3 and 2 with averages of 7.1 and 6.6 respectively fruits than the control that had an average of 5.7 fruits; other production-related variables are the length and diameter of the fruit, both treatment 3 is recording the highest values, as well: the average values for fruit were 16.59 cm and 15.39 cm diameter than the control that had the lowest average values with 13.40 cm and 12.38 cm diameter fruit. Likewise, in the moving average fruit weight is higher Q3, reaching a value of 3557.8 treatment kg / ha, followed by T2 with 2918.3 kg / ha, and the treatment had the lowest weight was the T0 he came only 2182.3 kg / ha., which corroborates the positive effect of the application of this type of liquid organic fertilizer, because if we contrast with the values reported by the analysis of organic fertilizers cause for investigation, conducted in Laboratory soil, plant tissues and waters of Central Experimental Station of the Amazon, is the wood vinegar liquid manure which has higher contents of macro and micronutrients, which has directly influenced the crop yield of cucumber variety Alaska. When it comes to accounting for T0 costs reach $ 398.20 in relation to investment in T3 which reached 889, $ 45, which undoubtedly and if this treatment is offset by the increase performance, being able to observe a ratio B / C increased with 0.41 for T3 T0 followed with 0.35 and finally the treatment Biol started with 0.11. Finally, the socialization of the results is made with farmers in the sector in the growth stages of the crop and a picnic with students.